Effect of niobium oxide (Nb2O5) addition to the physical and mechanical properties of cold isostatic press zirconia toughened alumina (ZTA)
Effect of niobium oxide (Nb2O5) addition to the physical and mechanical properties of cold isostatic press zirconia toughened alumina (ZTA) was investigated. Various amount of Nb2O5 (0 - 7 wt.%) were added into ZTA separately through solid state method. The influences of Nb2O5 addition were investigated on the structural, microstructural and mechanical properties of ZTA ceramics. XRD analysis identified the presence of t-ZrO2, m-ZrO2 and Nb2Zr6O17 phase in this system. The presence of Nb2Zr6O17 phase found to deteriorate the properties of ZTA ceramic, which is related to the solubility limit of Nb2O5. The optimum value was achieve at 1 wt.% Nb2O5, which gives the highest value for Vickers hardness (1840 HV), fracture toughness (8.60 MPa.m1/2) and flexural strength (351 MPa). The lower porosity results in the enhancement of the mechanical properties. Dense body was obtained via CIP method with the relative density achieve 99.8% to the theoretical density. The crack associated from indentation technique related with the increasing of fracture toughness value due to the presence of crack deflection. The phase transformation (t → m) also occurs in this system and resulted in improvement for fracture toughness and flexural strength. The obtained values indicated that Nb2O5 found to improve the physical and mechanical properties of ZTA ceramic. Thus, the high strength and toughness of ZTA ceramic can be produced.